Human placental suppressors of cytokine signalling (SOCS) and inflammatory cytokines are dysregulated in assisted reproduction, advanced maternal age and pre-term birth - S. J. Knight; A. D. Smith; H. Kim; A. C. Collier (IMR Press, 2020)
Summary of Investigation: Assisted reproduction technologies (ART) are now commonly used to conceive. ART is associated with higher incidence of negative birth outcomes which may be due to altered cytokine signaling. Materials and Methods: This pilot study evaluated the suppressors of cytokine signaling SOCS and levels of proinflammatory cytokines ART and non-ART placentas (n=14 each) matched for maternal and gestational age, delivery method, pregnancy weight gain, and body mass index. Comparisons of advanced maternal age (AMA), with or without pre-term birth (PTB) were included. SOCS1, 2, and 3 levels were evaluated with immunohistochemistry and IFN-γ, IL1-β, IL-6, IL-8, IL-10, and TNF-α with ELISA. Results: ART was associated with significantly lower SOCS3. Although SOCS1/IL-10 and SOCS2 and 3/IFN-γ significantly associated in normal conception, associations were lost in ART. In AMA, placental SOCS1 and 2 were associated with IFN-γ, and SOCS3 with IL-6, but under 35 these associations were lost. Term birth was associated with placental SOCS1 inhibition of IL-8 and SOCS2 induction of IL-10, but PTB was not. Conclusion: Cytokine signaling is dysregulated in human placentas by ART which might be a cause of negative reproductive outcomes in ART.